Determinación de la demanda máxima unitaria para clientes residenciales de las zonas urbanas en las categorías c, d y e del cantón Loja y su proyección a 10 años. - Guaillas Morocho, Danny Roberto (2021)
Determining the Maximum Projected Demand is important for a correct dimensioning of the distribution networks, to do this, the research carried out focuses on obtaining the current and projected Maximum Unit Demand (MUD) values for category C, D and E. Transformer load records are considered for a sector that is within each category and its respective historical consumption, a cluster analysis was implemented in order to obtain a more approximate probabilistic consumption value from a set of data. The current Maximum Unitary Demand was calculated and projected to 10 years taking into consideration growth rates of each sector, the demand values obtained for one (1) user are: category C: 1.4 kVA, category D: 0, 94 kVA and category E: 0.64 kVA. Keywords: Maximum Demand, Projected Maximum Unitary Demand, Transformer Loads, Cluster Analysis, Growth Rate.